Dairy profit projection model for the High Plains region - Schulte, Kristen (Kansas State University, 2011)
Structural change within the industry, improved management, and volatility in commodity markets are reasons to evaluate and monitor the dairy industry in the future. The dairy industry has shifted concentration of production between regions over time. The Southern High Plains region, including the states of Colorado, Kansas, Oklahoma, New Mexico, and Texas, has undergone cow inventory growth in the past ten years. Dairies have become more concentrated, management has become more refined, and the commodity markets have become more volatile. Education and tools are readily available to producers with issues on reducing production, animal health, and feed losses. Financial risk is a key area producers have limited knowledge and resources. Mitigating this risk is essential in today‟s marketplace to maximize gains and margins as well as create opportunities for the operation to succeed and be financially sound. There are several resources which approximate returns based on either a point in time reference or complete user input. This study allows users to reflect on 21 years of historical data, 1990-2010, as well as plug in their own data or use default market data to estimate projected returns over the next 12 months. This study also builds a modeling framework that will allow historical dairy returns to be estimated and future returns projected on a regular basis. Over time average herd size has grown to reduce cost per head and producers are more efficient, milk production per cow has increased to over 70 pounds per day. Historically prices have increased over time, but the spread between highs and lows has escalated. This model solidifies that milk price and production are key revenue drivers while feed, replacement costs, and labor are large cost components at 39, 17, and 6 percent, respectively. Additionally, changing market prices can intensify the gain or loss an operation will incur over the short term, the projection model shows 2011 just below breakeven due to strong commodity markets. Dairy operations in the Southern High Plains region have shown positive returns in 108 of 252, 43 percent, months with greatest negative annual returns 2006 and 2009.
Keywords: Dairy; Profit projection; Historical returns; Agriculture, General (0473); Economics, Agricultural (0503)